Best Evidence that UAP Source and Utilize High-Voltage Electric Energy for Hovering, Hyper-Fast Acceleration and Motion - Beck, Thomas E.; Colli, Janet E. (Journal of Scientific Exploration, 2025)
We investigate the best evidence of high-voltage UFO/Unidentified Aerial Phenomena (UAP) electrical properties to progress our understanding of the hyper-fast acceleration and travel of UAP in Earth’s atmosphere and in near-space. Based on that evidence, our findings show that UAP source and utilize high-voltage electric energy for hovering, and hyper-fast acceleration and motion. Furthermore, the design of these advanced technological systems may be based on natural, atmospheric electrical vortices and related electric discharge phenomena. We propose that some UAP powerplants are designed similar to natural tornadic-vortices. We establish the relevance of the following topics to the scientific study of specific classes of high-voltage electric UAP: the electro-coalescence of atmospheric water vapor; UAPs self-generated, high-voltage electromagnetic and electrostatic fields; rotating electric fields and super-high-voltage, electrostatic propulsion; and Unidentified SubmersibleObjects (USOs). The appearance of advanced technologies having to do with UAP may be relatively simple but overlooked plasma-based, electromagnetic and electrostatic technologies. UAP likely maneuver in Earth’s atmosphere by utilizing a simple form of high-voltage, electrostatic, propellant-less propulsion—allowing these craft to push off the locally ionized atmosphere. Evidence supports our hypothesis that UAP source and initiate the streaming of uninterrupted, carbon-free, Earth-ionosphere, solar plasma direct electric energy. Finally, we summarize advanced, super-high-voltage, electrostatic propulsion of UAP. The US Navy’s authentication (December, 2017) of leaked UAP videos validated hard evidence of UAP presence in global air spaces. Highly reliable witnesses have observed UAP exhibiting hyper-fast accelerations and motion within Earth’s atmosphere, as well as in low Earth orbit. Multi-witness visual and sensate observations combined with hard data from these cases provide insights into the development of hyper-fast travel dynamics and their solar plasma, electric energy source. We also report on new scientific standards of observation and recording in UAP research, including recommended detection equipment.